Evaluating Bone Health in Egyptian Children with Forearm Fractures: A Case Control Study. (29th August 2016) - El-Sakka, Abeer; Penon, Cristina; Hegazy, Adham; Elbatrawy, Salwa; Gobashy, Amr; Moreira, Alvaro
Abstract : Objective . To determine the likelihood of vitamin D deficiency and low bone mineral density in Egyptian children with forearm fractures. Methods . A case control study of 46 children aged 3 to 10 years with or without forearm fractures. Validated questionnaires were used to assess calcium and vitamin D intake as well as sun exposure. Serum calcium, phosphorus, alkaline phosphatase, and 25-hydroxy-vitamin D were collected. Bone mineral density was evaluated using dual-energy X-ray absorptiometry. Results . Compared to the Control group, calcium and vitamin D intake was lower in the Cases group (p = 0.03 ). Cases had higher Body Mass Index than Controls, p = 0.01 . Children in the Cases group had lower mean serum calcium values 8.3 ± 1.4 compared to 9.3 ± 1.1 in Controls (p = 0.01 ). Alkaline phosphatase was higher in Cases 265 ± 65.8 than Controls 226 ± 54.6 (p = 0.03 ). Vitamin D and bone mineral density scores were significantly lower in the Cases group (p < 0.05 ). Conclusion . Our data shows an increased rate of vitamin D deficiency and decreased bone mineral density in Egyptian children with forearm fractures.